Case Report: Neoadjuvant immunotherapy with pembrolizumab alone for bilateral upper tract urothelial carcinoma is a feasible strategy for kidney sparing and avoidance of hemodialysis - Chan, Wai-Nga; Huang, Yun-Ching; Ho, Dong-Ru; Chen, Chih-Shou (Frontiers in Oncology, 2022)
In Taiwan, the incidence of upper-tract urothelial carcinomas (UTUCs) is higher than in western countries (20%-31% vs. 5%-10%) as is bilateral disease. The standard management for high-grade UTUC is radical nephroureterectomy with bladder cuff excision and regional lymphadenectomy. The challenges in managing bilateral UTUCs are how to retain renal function and avoid permanent hemodialysis. We present two cases of developed bilateral high-grade renal pelvis urothelial carcinoma, cT3N0M0 stage III that revealed excellent results in tumor regression after three cycles of half-dose Pembrolizumab. One case received unilateral retroperitoneal laparoscopic nephroureterectomy with bladder cuff excision; thereafter, renal function has been good till now and the remaining right kidney has been free of tumor recurrence in the 3 years of follow-up. The other case, however, expired from an immune-related adverse event (irAE) 22 days after the third cycle of pembrolizumab, although tumor remission was evident also. Neoadjuvant pembrolizumab alone could be a potential strategy in selected biomarkers positive high-grade bilateral UTUC with remaining neglectable nephrotoxicity and may avoid permanent hemodialysis.